PEMILIBAN DAN PENGGUNAAN MEDIA DALAM PROSES PEMBELAJARAN - Sungkono Sungkono (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Learning media is an essential factor in improving learning quality. 'nusing media in learning process, educators must be selective in choosingthe kind of media she/he will use. The criteria ones must pay attention inchoosing learning media are: learning purpose, effectivenes:;, studentcharacte.-istics, availability, technical quality, flexibility, user skill andavailable time. The steps in choosing learning media are 1) learningactivity 2) message delivery 3) subject characteristics 4) mediacla.!sijication 5) media characteristics analysis. There are two models inusing /earning media: inside class and outside class. The procedures inusing learning media are preparation, implementation and follow up.